2018
DOI: 10.1111/jcmm.13627
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulphide increases pulmonary veins and atrial arrhythmogenesis with activation of protein kinase C

Abstract: Hydrogen sulphide (H2S), one of the most common toxic air pollutants, is an important aetiology of atrial fibrillation (AF). Pulmonary veins (PVs) and left atrium (LA) are the most important AF trigger and substrate. We investigated whether H2S may modulate the arrhythmogenesis of PVs and atria. Conventional microelectrodes and whole‐cell patch clamp were performed in rabbit PV, sinoatrial node (SAN) or atrial cardiomyocytes before and after the perfusion of NaHS with or without chelerythrine (a selective PKC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 59 publications
(107 reference statements)
0
7
0
Order By: Relevance
“…Transsulfuration primarily takes place in hepatocytes; however some studies suggest that it also can take place in human blood as endothelial cells have been shown to secrete CBS. Hydrogen sulfide (H 2 S) is produced during transsulfuration and has been linked to pulmonary vein and atrial arrhythmogenesis in rats [21,22]. By remethylation, Hcy is a precursor of S-adenosylmethionine (SAM), which is crucial for remethylation reactions.…”
Section: Potential Mechanisms 421 Transsulfuration and Methylationmentioning
confidence: 99%
“…Transsulfuration primarily takes place in hepatocytes; however some studies suggest that it also can take place in human blood as endothelial cells have been shown to secrete CBS. Hydrogen sulfide (H 2 S) is produced during transsulfuration and has been linked to pulmonary vein and atrial arrhythmogenesis in rats [21,22]. By remethylation, Hcy is a precursor of S-adenosylmethionine (SAM), which is crucial for remethylation reactions.…”
Section: Potential Mechanisms 421 Transsulfuration and Methylationmentioning
confidence: 99%
“…The PKC-mediated increases in I KATP and I NCX were also observed in atrial myocytes; however, such effects were only presented in left atrial myocytes but not right atrial myocytes. This interesting observation demonstrates that H 2 S can lead to increased interatrial dispersion, and therefore increases the risk of supraventricular arrhythmias (145). Noted that PKC may also regulate other channels in addition to I KATP and I NCX , such as I to (146), I NaL (147), I Ks (148), and their potential roles in H 2 S-induced arrhythmias warrants further investigation.…”
Section: Potential Proarrhythmic Mechanismsmentioning
confidence: 86%
“…The mechanism of proarrhythmic effects of H 2 S can be more complicated in the atria. Recently, Chan et al performed a comprehensive investigation on the influences of H 2 S on the atria and provided novel insights into the proarrhythmic effects of H 2 S (145). The study reported that NaHS (H 2 S donor) significantly reduced sinoatrial node (SAN) beating rates, causing SAN dysfunction and potentially the AF.…”
Section: Potential Proarrhythmic Mechanismsmentioning
confidence: 99%
“…Micropipettes were filled with a solution containing KCl (140 mmol L −1 ), MgCl 2 (1.0 mmol L −1 ), HEPES (10 mmol L −1 ), EGTA (5 mmol L −1 ) and GTP (0.1 mmol L −1 ; pH adjusted to 7.3 with KOH). I KATP was elicited through depolarization in 10‐mV steps from a holding potential of −40 mV to test potentials between −100 and +100 mV for 300 ms at a frequency of 0.5 Hz 58 …”
Section: Methodsmentioning
confidence: 99%